Changing Dynamics of Urbanization and Social Inequality: A Case Study of Informal Settlements in Bangkok, Thailand - Ramatim Changsoo (International Journal of Science and Society, 2023)
The research embarked on a journey to unravel the intricate relationship between urbanization dynamics and social inequality within the context of informal settlements in Bangkok. Using a mixed methods approach, this research combines a quantitative survey and qualitative interviews. Demographic data is collected through a survey, which captures a socio-economic profile. Qualitative insights were obtained from in-depth interviews and observations, which provide a different understanding of residents' life experiences. This research not only illuminates the interplay between urbanization and social inequality within Bangkok's informal settlements but also amplifies the call for inclusive urban development that ensures the benefits of progress reach every corner of the city, irrespective of socio-economic background.